Analisis Risiko Pemasaran Pedagang Sembilan Bahan Pokok (Sembako) di Pasar Pinasungkulan Karombasan - Charles Rejnaldo Ngangi; Ivanca Maleakhi Lukow; Gene Henfried Meyer Kapantow (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2026)
This study aims to conduct an in-depth analysis of the marketing risks faced by sembako traders at Pinasungkulan Market, Manado. As nine essential commodities, sembako play a vital role in the daily lives of Indonesian society; however, their marketing in traditional markets is confronted with various challenges. The study employs the Failure Mode and Effect Analysis (FMEA) approach to identify, evaluate, and prioritize these risks. The research methodology includes a survey of sembako traders at Pinasungkulan Market using questionnaires, interviews, and observations. The collected data were analyzed descriptively and qualitatively using the FMEA tool, which assesses three main risk indicators: Severity, Occurrence, and Detection. The results of this analysis were used to calculate the Risk Priority Number (RPN), which serves as the basis for determining the priority of risk management. The findings indicate that the risk of inconsistent product quality is the highest priority, with the highest RPN value of 16.95. This is due to consumers’ sensitivity to variations in sembako quality, which affects trust, loyalty, and sales volume. Market risk ranks second (RPN 10.33), driven by price fluctuations, changes in demand, and competition. Operational risk (RPN 9.87) relates to technical disruptions and supply delays, while capital risk (RPN 9.17) is relatively lower, as traders are generally able to adjust the scale of their business according to available capital.